A bibliometric review of naturalist environmental education, 1937–2023 - Liu, Xie; Hussein, Mohd Kher; Mat Noor, Mohd Sallehuddin (Editura Universitatii din Oradea, 2024)
The significance of naturalist environmental education (NEE) which primarily focuses on human-nature relationships lies in its ability to mitigate detrimental influences on environmental quality and foster environmental awareness, thereby averting adverse ecological consequences. Through a bibliometric examination of the literature using Scopus, this research attempted to chart and evaluate the intellectual production associated with NEE. The findings are based on a statistical analysis of 1553 documents using the VOSviewer software. Results indicate there has been a significant increase in global scholarly focus on NEE and the pattern of publications trend follows a four-stage progression. "Social Sciences" has the greatest number of relevant articles. Keywords including education literacy and sustainable development are of utmost importance. There is clear evidence of global scientific collaboration among developed countries. It's crucial for scholars to prioritize interdisciplinary collaboration within NEE, and enhance adult environmental literacy on developing countries.